MANAJEMEN PEMBELAJARAN BAHASA INGGRIS DALAM MENINGKATKAN KEMAMPUAN WRITING SISWA SMP - Didharianti Kusuma; Zakaria Zakaria; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The purpose of this study is to describe management of teaching and learning English to improve writing skill of student at Junior High School 4 of Bengkulu City. The data collected by using instrument such as observation, interview and documentation The result of the research shows that firstly teacher prepares lesson plan based on the syllabus of curriculum 2013. Secondly, teacher implements learning activity to improve writing skill uses scientific approach and discovery learning model. Teacher uses Learning process integrated to other skill such as speaking and reading comprehension, also supporting skill such as grammar and vocabulary. Teacher also improves students’ vocabulary by making a mini dictionary in every meeting, gives motivation and clear instruction about social function, generic structure and language features of a functional text.